2005
DOI: 10.1103/physreve.71.066127
|View full text |Cite
|
Sign up to set email alerts
|

Void formation and roughening in slow fracture

Abstract: Slow crack propagation in ductile, and in certain brittle materials, appears to take place via the nucleation of voids ahead of the crack tip due to plastic yields, followed by the coalescence of these voids. Postmortem analysis of the resulting fracture surfaces of ductile and brittle materials on the microm-mm and the nm scales, respectively, reveals self-affine cracks with anomalous scaling exponent zeta approximately = 0.8 in 3 dimensions and zeta approximately = 0.65 in 2 dimensions. In this paper we pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…This process is associated with a length scale ξ c characteristic of the distance of the damage element from the tip. A plausible physical picture for such a process was proposed in [5,6]. The idea is to identify ξ c with the size of the plastic zone that develops near the crack tip due to the large stresses concentrated there.…”
Section: Damage Nucleationmentioning
confidence: 99%
See 4 more Smart Citations
“…This process is associated with a length scale ξ c characteristic of the distance of the damage element from the tip. A plausible physical picture for such a process was proposed in [5,6]. The idea is to identify ξ c with the size of the plastic zone that develops near the crack tip due to the large stresses concentrated there.…”
Section: Damage Nucleationmentioning
confidence: 99%
“…Model A was studied in Refs. [5,6] . In the absence of precise knowledge of the activation process we adopted reasonable probability distribution functions f (P (r)− P c ) and demonstrated that the cracks generated by the model were self-affine with ζ = 0.66 ± 0.03 irrespective of the specific form of f (P (r) − P c ).…”
Section: Growth Rule and Disordermentioning
confidence: 99%
See 3 more Smart Citations